1995
DOI: 10.13031/2013.27858
|View full text |Cite
|
Sign up to set email alerts
|

Simulating NO3-N Transport to Subsurface Drain Flows as Affected by Tillage Under Continuous Corn Using Modified RZWQM

Abstract: The Root Zone Water Quality Model (RZWQM) was previously modified to simulate subsurface drain flows and evaluate the impact of different tillage systems on subsurface drain flows (Singh and Kanwar, 1994). This article discusses further modifications made in the RZWQM to simulate nitrate-nitrogen (NO3-N) concentrations and NO3-N losses with subsurface drain flows. Daily NO3-N concentrations were simulated in subsurface drain flows under four different tillage systems: chisel plow (CP), moldboard plow (MB), not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 6 publications
0
20
0
2
Order By: Relevance
“…The earlier version of RZWQM was also used to simulate the effects of the four tillage practices on subsurface NO 3 ±N concentrations and losses (Singh and Kanwar, 1995b), but the model had not been previously used to compute an entire N balance for this research site.…”
Section: Simulation Modelingmentioning
confidence: 99%
“…The earlier version of RZWQM was also used to simulate the effects of the four tillage practices on subsurface NO 3 ±N concentrations and losses (Singh and Kanwar, 1995b), but the model had not been previously used to compute an entire N balance for this research site.…”
Section: Simulation Modelingmentioning
confidence: 99%
“…During the 4 years of RZWQM integration with MSEA field research, the model was tested for: 1) water and pesticide movement at the Minnesota MSEA site (Wu et al, 1999); 2) surface runoff, nitrate and pesticide losses to seepage and runoff, and crop yields at the Missouri MSEA site (Ghidey et al, 1999); 3) crop yield, and water, nitrate and pesticide movement at the Iowa MSEA site (Jaynes and Miller 1999); 4) crop yield, N uptake, plant biomass, leaf area index, soil water content, and soil N at the Nebraska MSEA site (Martin and Watts 1999); and 5) leaf, stem, and seed biomass of corn at the Ohio MSEA site (Landa et al, 1999). Although the model has been evaluated extensively under tiledrained conditions at Nashua, Iowa for estimating N loss and crop growth (Singh and Kanwar, 1995;Kumar et al, 1998;Bakhsh et al, 2004a,b), only a few years of data or a few treatments were used (Ma et al, 2007a).…”
Section: Introductionmentioning
confidence: 99%
“…The Brooks-Corey soil water retention parameters also affected only tile flow not yield in their study. For Iowa conditions, Kumar et al (1998Kumar et al ( , 1999 and Singh and Kanwar (1995) found that LK sat and drainable porosity (soil porosity -soil water content at 1/3 bar) were the most sensitive variables in simulating tile drainage flow.…”
Section: Introductionmentioning
confidence: 99%